1996
DOI: 10.1021/np9603939
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 5-(3-Hydroxypropyl)-7-methoxy-2-(3‘-methoxy-4‘-hydroxyphenyl)-3- benzo[b]furancarbaldehyde, a Novel Adenosine A1Receptor Ligand from the Root ofSalvia miltiorrhiza

Abstract: A novel adenosine A1 receptor ligand, 5-(3-hydroxypropyl)-7-methoxy-2-(3‘-methoxy-4‘-hydroxyphenyl)-3-benzo[b]furancarbaldehyde (1), is a constituent of the roots of Salvia miltiorrhiza. Through biomimetic considerations, methyl ferulate was used as starting material for an eight-step synthesis of 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The product was reprotected with a benzyl group, treated with diisobutyl aluminum hydride in dry tetrahydrofuran, selective-oxidized with manganese dioxide in ethyl acetate, and then finally deprotected with titanium tetrachloride in dichloromethane to obtain the target molecule as a yellowish solid. The desired product was confirmed by 1 H NMR and electron ionization/mass spectrometry and gave spectral data identical with literature values (Yang et al, 1991(Yang et al, , 1992Kuo and Wu, 1996) Cell Lines. Human oral epidermoid carcinoma KB cells, nasopharyngeal carcinoma HONE-1 cells, colorectal carcinoma HT29 cells, nonsmall cell lung cancer H460 cells, and glioblastoma multiforme DBTRG cells were maintained in RPMI 1640 medium supplied with 5% fetal bovine serum.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The product was reprotected with a benzyl group, treated with diisobutyl aluminum hydride in dry tetrahydrofuran, selective-oxidized with manganese dioxide in ethyl acetate, and then finally deprotected with titanium tetrachloride in dichloromethane to obtain the target molecule as a yellowish solid. The desired product was confirmed by 1 H NMR and electron ionization/mass spectrometry and gave spectral data identical with literature values (Yang et al, 1991(Yang et al, , 1992Kuo and Wu, 1996) Cell Lines. Human oral epidermoid carcinoma KB cells, nasopharyngeal carcinoma HONE-1 cells, colorectal carcinoma HT29 cells, nonsmall cell lung cancer H460 cells, and glioblastoma multiforme DBTRG cells were maintained in RPMI 1640 medium supplied with 5% fetal bovine serum.…”
Section: Methodssupporting
confidence: 74%
“…Salvinal (Fig. 1) was synthesized at the Department of Chemistry, National Taiwan University (Taipei, Taiwan) with use of the method described by Kuo and Wu (1996). In brief, methyl ferulate was oxidized in acetone solution with aqueous ferric chloride to yield dihydrobenzofuran.…”
Section: Methodsmentioning
confidence: 99%
“…These compounds were synthesized employing previously procedures reported with modifications. [24][25][26] All the structures were confirmed on the basis of NMR, EI-MS and IR data and comparison with the literature.…”
Section: Synthesis Of Dihydrobenzofuran Neolignans 1-8mentioning
confidence: 67%
“…It has been reported that diferulate 5 can be obtained in 30% yield from radical coupling of ferulate by ferric chloride oxidation in aqueous acetone. 28 However, we were not able to obtain the claimed yield for diferulate 5 by following the exact procedure described in that paper. Instead, only 5% of diferulate 5 was isolated because huge amounts of unreacted starting materials remained.…”
Section: ■ Results and Discussionmentioning
confidence: 87%